Passively mode-locked ytterbium-doped fiber laser operation with few layer MoS2 PVA saturable absorber - Al-Masoodi, Ahmed Hasan Hamood; Ahmed, Mahmoud Hazzaa M.; Latiff, Anas Abdul; Azzuhri, Saaidal Razalli; Arof, Hamzah; Harun, Sulaiman Wadi (Elsevier, 2017)
A passive mode-locked Ytterbium-doped fiber laser (YDFL) is experimentally demonstrated using a multi-layered molybdenum disufide (MoS2) as a Saturable Absorber (SA). The MoS2 film was obtained based on a liquid phase exfoliation of MoS2 crystal. A small slice of MoS2 film was sandwiched in between two optical ferrules via a fiber adapter and linked into an YDFL cavity to generate a stable mode-locked operation at a wavelength of 1073.86 nm with repetition rate of 18.8 MHz. At pump power of 202.9 mW, the maximum pulse energy of 0.1 nJ was achieved with an output power of 1.84 mW. The MoS2 film was fabricated through a simple process and it has a modulation depth of 9.7% and saturating intensity of 40 MW/cm2.